Las aulas virtuales como herramienta para mejorar el aprendizaje significativo - Guilcazo Suntásig, Rocío Jeannett (2017)
The present research work based on the “virtual classrooms as a tool in order to improve meaningful learning” with the purpose of collecting data about the virtual classrooms and their contribution in the improvement of learning of students at “Cacique Tumbala” Millennium Educational Unit a diagnostic that will contribute that future research gives adequate utility. The goal of this research is to strengthen the teaching-learning process through researching the benefits of virtual classrooms within the educational environment in students that is why it applied a deductive methodology, the same that will use with research objectives, The inductive method will apply to do the theoretical framework and establish conclusions and recommendations also it performed the constructivist paradigm in the theory of the project although it did an analysis criteria in each theme, the same way it used the survey and the interview as the techniques with their questionnaire in order to obtain information and know different virtual classrooms This research work to its end will generate a practical contribution which consists in establishing important data referring in a virtual education of quality that will allow to future researchers develop strategies and tools in order to improve the coexistence and development of subjects class achieving a social impact and students will be in permanent communication through chats, videoconferences, forums, etc….